High frequency magnetic properties of polymer-bonded Terfenol-D composites - Pasquale, M; Lim, SH (AMER INST PHYSICS, 1999)
We measure the high frequency magnetic properties of polymer-bonded Terfenol-D rods compacted from powders of different size, in order to analyze the effect of structure and preparation conditions in sonic or ultrasonic frequency applications. Magnetic characterization at high fields and in the kilohertz range is made using a custom built amorphous metal yoke. Experimental data are analyzed using the theory of losses and the dynamic Preisach model. The electrical resistivity is estimated to be about 1.25 mu Omega m, higher than in grain-oriented materials. The classical contribution to dynamic power loss, directly proportional to conductivity, is found to be dominant. The analysis establishes a direct connection between static and dynamic magnetic properties and structural characteristics, such as the density, conductivity, and the powder size, which can be modified for optimization purposes. (C) 1999 American Institute of Physics. [S0021-8979(99)21308-4].
Keywords: POWER LOSSES; HYSTERESIS